AKTIVITAS HIPOGLIKEMIK EKSTRAK ROSELA (Hibiscus sabdariffa L.) PADA TIKUS PUTIH DIABETES - Adhy Nugroho, Christianto (Widya Warta, 2010)
Rosela is one of medicinal herbs. The aim of the study was to find out the hypoglycemic effect of oral intake of Rosela extract on diabetic white rat. This research apllied Complete Randomized Design of four groups with five replications to each. The treatment for those groups was: no treatment, insulin 5 unit/kg body weight, 250 mg/kg body weight of Rosela extract, and 500 mg/kg body weight of Rosela extract. The parameters used were fasting blood glucose concentration and blood glucose concentrations at the 60th and 120th minutes. The result showed that the extract of Rosela decreased blood glucose concentration. The treatment with Rosela extract 250 mg decreased blood glucose concentrations as much as 24,32%, whileÂ  that with Rosela extract 500 mg decreased blood glucose concentration as much as 32,44%.